Produção de etanol de 2ª geração por Dekkera bruxellensis a partir de hidrolisado de bagaço de cana-de-açúcar - Codato, Carolina Brito (Universidade Federal de São Carlos, 2013)
Bioethanol is an alternative low cost fuel, which is conventionally obtained in Brazil from the fermentation of sugarcane juice, molasses, or a mixture of these. However, alternatively, ethanol could be obtained from lignocellulosic materials, wastes or agroindustrial byproducts composed of cellulose, hemicellulose and lignin, such as sugarcane bagasse. For each ton of cane processed, 250 kg of bagasse are obtained on average, which is usually burned for power generation industry. The microbial cultivation using these materials depend on the availability of substrates, accordingly, acid hydrolysis has been considered one of the most widely used process for the depolymerization of the hemicellulose fraction of lignocellulosic materials, due to their low cost and high efficiency. However, under conditions of high temperature and pressure, glucose and xylose released are degraded to 5- hydroxymethylfurfural (HMF) and furfural, respectively. These compounds are characterized by inhibiting the yeast used in the fermentation step, which influences the microbial metabolism and the conversion of hexoses and pentoses obtained in ethanol. In this context, the aim of this work was to evaluate the ability of a yeast strain, from the species Dekkera bruxellensis (CCA155) in producing ethanol from sugarcane bagasse hydrolysates, since it has shown to be a yeast tolerant to adverse conditions found in industrial fermentation processes. The results indicated that D. bruxellensis was capable of producing ethanol in a synthetic medium containing xylose or arabinose, and xylose or glucose as sole carbon sources, and when grown in concentrations of 50 or 100% sugarcane bagasse hydrolyzate, maximum specific speeds growth was similar, about 0.009 h-1, with cell productivity of about 0.035 gL-1h-1. In the bioreactor tests, the yeast displayed low specific growth rate during the first five days, 0.003 h-1, caused by a slow consumption of glucose. But in a second phase of growth, with a lower rate 0.001 h-1, there was an increase in xylose consumption, a period in that an increase in ethanol concentration with maximum yield of approximately 3.25 mg/L.h was observed. Therefore even with lower growth when compared to yeast fermentation conventionally used in ethanol industries, these results suggest the feasibility of the cultivation of D. bruxellensis in hydrolysates of sugarcane bagasse.
Keywords: Fermentação; Dekkera bruxellensis; Resíduos lignocelulósicos; Fermentação etanólica; Bagaço de cana-de-açúcar; Waste lignocellulosic; Ethanol fermentation; Sugarcane bagasse; CIENCIAS AGRARIAS